BRCA1 methylation in breast duct carcinoma, a practical study in Duhok-Iraq: BRCA1 methylation in breast duct carcinoma - Hasan, Narmeen Adalat; Pity, Intisar Salim (Cellular and Molecular Biology, 2023)
Lacking protein functions of Breast cancer susceptibility gene1 (BRCA1) and Breast cancer susceptibility gene2 (BRCA2), by methylation, represents tissue-specific silent epigenetic regions that tolerate genomic instability and may end in different cancers, mainly breast and ovary. Promoter-CpG island hypermethylation is a common molecular defect in cancer cells. This has prompted us to use MSP for identification of BRCA1 methylation in these groups of women at Duhok, north of Iraq. Genomic DNA was isolated from 96 tumor samples from patients with primary breast cancer and normal tissues which include; 40 non-neoplastic breast tissues (considered as external control) and 40 distant non-cancerous tissues from the same cancerous women (internal control). The extracted DNA was subjected to methylation-specific PCR (MSP) to determine the promoter methylation status of BRCA1 and its correlation with study parameters including protein expression level of ER, PR, Her2/neu, and Ki67 receptors. The study revealed 10.4% complete BRCA1 methylation and 66.6% partial methylation (PM) among the cancerous samples. Partial methylation was observed in 95% of internal control and 20% of the external control. Complete methylation was negative in both control groups. Compared with negative methylation, positive BRCA1 promoter methylation was significantly high among triple negative (ER-, PR-, Her2-) cases with high proliferative index. There was also a methylation trend toward cases with T2 and higher staging status, although didn’t reach the level of significance. BRCA1 promoter complete methylation was exclusive for cancerous tissues. With management of the above concerns, this line of research gains a strength point including the prevalence of DNA methylation changes among sporadic breast cancer (i.e. not restricted to the inherited type). Considering partial or focal BRCA1 methylation, caution has to be taken as this epigenetic alteration, which may progress to complete methylation status, was detected in non-neoplastic breast tissues adjacent to the cancerous ones and even normal breasts. This triggers application of extended screening programs, including BRCA1 methylation, for identification of women at risk, and can benefit from early intervention.